2012
DOI: 10.1007/s00068-012-0198-6
|View full text |Cite
|
Sign up to set email alerts
|

Immediate thoracotomy for penetrating injuries: ten years’ experience at a Dutch level I trauma center

Abstract: Background An emergency department thoracotomy (EDT) or an emergency thoracotomy (ET) in the operating theater are both beneficial in selected patients following thoracic penetrating injuries. Since outcome-descriptive European studies are lacking, the aim of this retrospective study was to evaluate ten years of experience at a Dutch level I trauma center. Method Data on patients who underwent an immediate thoracotomy after sustaining a penetrating thoracic injury betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 41 publications
0
37
0
6
Order By: Relevance
“…Van Waes et al reported on 56 patients undergoing an EDT for penetrating trauma over a 10-year period in the Netherlands. 6 Only 12 patients underwent an EDT in this study with 3 (25%) survivors. 6 Likewise, Lustenberger et al reported the experience of a level 1 trauma centre in Switzerland over a 12-year period and found 10 survivors (20%) from 49 EDTs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Van Waes et al reported on 56 patients undergoing an EDT for penetrating trauma over a 10-year period in the Netherlands. 6 Only 12 patients underwent an EDT in this study with 3 (25%) survivors. 6 Likewise, Lustenberger et al reported the experience of a level 1 trauma centre in Switzerland over a 12-year period and found 10 survivors (20%) from 49 EDTs.…”
Section: Introductionmentioning
confidence: 97%
“…6 Only 12 patients underwent an EDT in this study with 3 (25%) survivors. 6 Likewise, Lustenberger et al reported the experience of a level 1 trauma centre in Switzerland over a 12-year period and found 10 survivors (20%) from 49 EDTs. 7 The survival for penetrating trauma was 70% (7 of 10 patients), and the survival for blunt was 7.7% (3 of 39 patients).…”
Section: Introductionmentioning
confidence: 97%
“…In our opinion terms such as immediate and urgent may obscure these studies [34,12]. The operative procedures and clinical outcomes in the studies using this kind of terminology is not applicable to a true emergency setting where an ET is split second decision, and a desperate attempt to save a patient in extremis.…”
Section: Discussionmentioning
confidence: 99%
“…Í leiðbeiningum Advanced Trauma Life Support (ATLS) frá árinu 2008 er bent á að árangur við bráðan brjóstholsskurð sé bestur við hnífáverka, en síðri við skotáverka og sljóa áverka eins og eftir umferðarslys eða fall. 6 Fjöldi rannsókna hefur staðfest góðan árangur við hnífstunguáverka sem bundnir eru við hjarta 4,7,8 og í nýlegri rannsókn frá Osló lifðu 45% sjúklinga af áverka á hjarta á 10 ára tímabili, sem þykir einstakur árangur. 1 Þetta er ekki fyrsta aðgerðin sem gerð er með þessum haetti hér á landi.…”
Section: Umraeðurunclassified
“…Meðferð hans var mjög svipuð þeirri sem beitt var í þessu tilfelli og lifði hann einnig aðgerðina af án fylgikvilla. Góður árangur við þessar aðgerðir hér á landi er í samraemi við nýlegar rannsóknir frá Sviss og Hollandi 7,8 en einnig borið saman við norska rannsókn þar sem 18% sjúklinga lifðu af bráðan brjóst-holsskurð vegna áverka af ýmsum orsökum. 10 Sammerkt þessum erlendu rannsóknum er að brjóstholsskurðlaeknar framkvaemdu flestar aðgerðirnar, líkt og hér á landi, sem gaeti að hluta til skýrt góðan árangur.…”
Section: Umraeðurunclassified